Perlindungan Hukum Terhadap Data Pribadi bagi Nasabah Pinjaman Online - Duwi Rindiantika, Wafia; Laily Mufid, Firda; Winiari Wahyuningtyas, Yuli (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2023)
Online lending or peer to peer landing as a form of financial technology is the result of technological advances that offer many loans with easier and more flexible terms and conditions when compared to conventional financial institutions such as banks. But it turns out that behind this convenience, of course there are consequences and risks that will be received by borrowers if they violate their obligations. In the last few years to date, the OJK, which is part of the Investigation Alert Task Force, still finds and blocks illegal online loan services, because they cause many problems for their users, several cases have ended with borrowers ending their lives because they cannot be strong enough to be billed by debt collectors. Apart from that, the problem with online loans after billing with terror is the transfer of contacts. Blender can read all cellphone transactions and photos. So that the protection of personal data is still low. Indonesia does not yet have a personal data protection law, so that business actors go around with online loan users.